Peningkatan Prestasi Belajar Seni Budaya Materi Menggambar Flora, Fauna, dan Alam Benda Melalui Model Pembelajaran Kontekstual pada Siswa Kelas VII C SMP Negeri 2 Panggul Trengalek - Jatmika, Surya Hadi Widi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to obtain objective answers about improving learning achievement in Art and Culture material for Drawing Flora, Fauna, and Nature through a contextual learning model for class VII C students in Semester 1 of the 2019/2020 academic year at SMP Negeri 2 Panggul. This research is a descriptive qualitative research type Classroom Action Research will be presented in the form of a cycle. Each cycle consists of four stages, namely (1) planning. (2) implementation or action, (3) observation, (4) reflection. This study uses one instrument, namely a test. The test instrument was used to collect achievement data. The results of the first cycle test and the second cycle test results on the Drawing Flora, Fauna, and Nature materials that have been analyzed and can be compared. In the first cycle of learning, the test results are still low when compared to the results of the second cycle of tests. This is evidenced by the results of the first cycle test, the total score is 2220 with an average score of 74 and the percentage of completeness is 73%, while the second cycle test results total 2410 with an average value of 80.33 and a percentage of completeness 90%. Thus it can be said that the results of the second cycle of research have increased from the results of the first cycle of research.